Investment risk and efficiency analysis of Croatian pension funds - Mateo Krcić; Valentina Kolačko; Ivana unek Kokotec (UTMS Journal of Economics, 2021)
The object of this study is to analyze investment efficiency of pension funds by examining the portfolios of four mandatory pension funds (AZ, Erste Plavi, PBZ Croatia osiguranje and Raiffeisen). In this study, the pension system is analyzed through two step procedure. The study will first focus on pension fund portfolios, models of investments and risks that should be taken in account. Also, legal regulations are described which outline the business framework of pension funds and systems. After legal regulations short literature review is also given. Secondly, there will be an analysis of the current portfolios of pension funds and it will be tested whether they can be optimized by means of a mathematical maximization formula. In order to analyze the impact of pension funds, it was necessary to overview lists of the investments undertaken by the four mandatory pension funds in the period from 2015 to 2019. The analysis of investment optimization, together with the method for a mathematical return maximization in pension funds of category A and B, has found that there is room for increasing investments in stocks and consequently maximize returns.
Keywords: M30; 330; pension funds; optimization; portfolio management; risk analysis; share return